Meaning in language an introduction to semantics and pragmatics - Cruse, D. A. (Oxford textbooks in linguistics, 2011)
This book provides a comprehensive introduction to the ways in which meaning is conveyed in language, covering not only semantic matters but also topics normally considered to fall under pragmatics. Above all, the book displays and explains the richness and subtlety of meaning, with the aid of numerous examples and exercises throughout the text. Highly readable, written with style and wit, Meaning in Language is not bound to any particular theory, but provides explanations of theoretical approaches and perspectives as the context requires, with a stress throughout on the need for conceptual clarity. The text and exercises in this third edition have been fully updated to take into account the most recent developments in the field and new chapters have been added, one on the semantics of prepositions and another on the semantics of derivational affixes.